Analisis Perbandingan Proyeksi Kinerja Reksadana Syariah dan Konvensional Era Postcovid Berdasarkan Nilai Aktiva Bersih - Anshori, Arif Rijal; Rohmah Maulida, Ira Siti; Himayasari, Neng Dewi (Jurnal Ilmiah Ekonomi Islam, 2022)
At this time pandemic covid-19 is depressing the position of the financial market and banking sector. But, this is different from non-bank financial institutions, namely mutual funds, which have increased both sharia and conventional. The purpose of this study is to examine how the projections of the financial performance of Islamic and conventional mutual funds for the next 6 years. The method used is quantitative with a descriptive approach, data processing is done by projection analysis using excel. The results of this study are 1) The performance of Islamic mutual funds during the early post-covid era has decreased, while conventional mutual funds have increased every year, including in the early post-covid era. 2) Projected performance of Islamic mutual funds based on net asset value (NAV) in the post-covid era for the next 6 years will continue to increase by reaching the highest point in 2027 of 102,054.28, while conventional mutual funds will experience a decline in year 2 of the post-covid era with projected net asset value amounted to 651,214.34 and in the 3rd to 6th year it will continue to increase